Assessing chemical properties and heavy metals in groundwater resources in a developing country: a baseline study - Md. Saiful Islam; Md. Kawsar Ahmed; Abdullah Al Bakky; Zulhilmi Ismail; Khalid A. Ibrahim; Abubakr M. Idris (Scientific Reports)
Abstract Less information is available on the physicochemical properties conferring groundwater quality in the ancient Capital of the Pundranagar region, Bangladesh. This study preliminarily evaluates the quality of groundwater beneath rivers, ponds, and rice fields in northern Bangladesh. Probable causes of heavy metals contamination in groundwater, health hazards, and spatial variations were evaluated. The concentration of nitrate nitrogen (NO3-N) was observed as 74.05, 82.87, and 53.90 mg/L, respectively, for the field, pond, and river site, which was higher than the World Health Organization’s recommended limit (50 mg/L). The amounts of heavy metals in groundwater, such as As, Cd, Pb, Cr, Ni, Cu, Mn, and Zn, ranged from 0.012 to 0.25, 0.012–0.087, 0.015–0.097, 0.014–0.098, 0.012–0.304, 0.006–0.086, and 0.015–0.996 mg/L, individually. Based on the estimated value of water quality index (WQI), the quality of the analyzed groundwater was classified as “excellent” to “poor”, which varied from 48.57 to 58.88. The pollution status of groundwater followed in the descending order of field site > river site > pond site. Severe contamination from manufacturing and farming operations was indicated for heavy metals enrichment in groundwater. Ingestion and skin contact with Cd and As through groundwater provide the greatest danger to residents for both non-carcinogenic and carcinogenic health impacts. The results demonstrate that the groundwater quality is insufficient for sustaining aquatic life and is unsafe for human consumption, thereby posing health hazards to the local population.